Same Season and Carry-Over Effects of Source-Sink Adjustments on Grapevine Yields and Non-structural Carbohydrates - Martínez-Lüscher, Johann; Kurtural, Sahap Kaan (Frontiers in Plant Science, 2021)
The grapevine (Vitis vinifera L.) is managed to balance the ratio of leaf area (source) to fruit mass (sink). Over cropping in grapevine may reveal itself as spontaneous fruit abortion, delayed ripening or as alternate bearing. The aim of this work was to study the same season and carry-over effects of manipulating source to sink ratios on grapevine phenology, leaf gas exchange, yield components, berry soluble solids accumulation and reserve carbohydrate and soluble sugar concentration in roots. Cabernet Sauvignon grapevines were subjected to defoliation (33%, 66% and 100% of the leaves retained) and fruit removal treatments (33%, 66% and 100% of clusters retained) arranged in a factorial design. Results from two seasons of source-sink manipulations were substantially different. In both seasons defoliation treatments affected season-long net carbon assimilation (AN) and stomatal conductance (gs) where the less leaves retained resulted in greater AN and gs and fruit removal had no impact on leaf gas exchange. In the first season, leaf area to fruit mass was hardly related to berry soluble solids and in the second season they were strongly correlated that suggested a degree of acclimation. Defoliation treatments had great impacts on berry size, berries per cluster and total soluble solids in both years. Fruit removal treatments only had effects on berry mass and berries per cluster in the first season, and only on berry soluble solids in the second. The predominant effect of defoliation (carbon starvation) cascaded onto reducing root starch content, root mass and delaying of veraison and leaf senescence, as well as harvest which was delayed up to 9 weeks with 33% of the leaves retained. In a third season, where grapevines grew without treatments, defoliation treatments had resultant carryover effects, including reduced leaf area, number of berries per cluster, clusters per vine, and yield but not on leaf gas exchange dependent on previous seasons’ severity of defoliation. Balancing source-to-sink ratio is crucial to obtain an adequate speed of ripening. However, this was the culmination of a more complex whole-plant regulation where the number of leaves (source strength) outweighed the effects of fruits (sink strength).